Preliminary Design Study of Thorium(Th) and Protactinium ( 231 Pa) Based Fuel for Tight Lattice Long Life BWR - Eka Sapta Riyana; Zaki Su’ud (Indonesian Journal of Physics, 2005)
A preliminary design study for the utilization of thorium based fuel loaded with 231Pa on tight lattice BWR type reactor has been performed. Protactinium-231 has very interesting neutronic properties, which enable the core to reduce initial excess-reactivity and simultaneously increase production of 233U to 231Pa in burn-up process. Optimizations the content of 231Pa in the core enables the BWR core to sustain enough reactivity for long period of time with reasonable burn-up reactivity swing. Based on the optimization of fuel element composition (Th and Pa) in low moderation environment (tight lattice core) can be achieved reactor core with longer operation time, 20 ~ 30 years operation without fuel shuffling or refueling, with average power densities of about 35 watt/cc.